As infâncias e o brincar no contexto escolar: alguns contrastes entre a cultura lúdica e as práticas pedagógicas - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
This study sought to investigate how children live and construct their infant cultures at school through play, and understand in which manner the teachers establish their teaching practices in these social and cultural relationships. This investigation contemplates the studies into children as a theoretical mosaic constructed historically to understand and discipline the child, in which it is possible to find the echoes of the theories and conjectures constructed in the past that, in relation to the child’s imagination, provide information that modern society was able to subtract the creative imagination and its spaces for participation, in the way it ended up being submitted to the control of adults and a rigid, suffocating, disciplinary program, in daily school life. Such truths about children and infancy repeat themselves, however they have transformed themselves because starting from the understanding of the architects of the Sociology of Infancy, among those such as Allison James and Alan Prout, 2003/2004; Corsaro,1997; Delgado and Müller, 2005; Manson 2001; Pinto and Sarmento, 1999; Saramago, 2000; Wajskop, 1999, the child, in current scientific works, has assumed a role as the subject of in these spaces, and strengthening the space of the protagonist in the socio-cultural constructions, with his or her peers as well as family relationships, as well as in the self-determination and alterity or even in what is considered giving the child a voice. Starting from these suppositions, this study is organized via three themes: The concept of the child and infancy and the relationship with play; Play in infancy in school; Play in regard to pedagogical practices. From these analyses, this study looked at analyzing the construction of these relationships that are established between the production of play culture and pedagogical practices elaborated by the teachers, seeking to understand the conceptions of infancy, play and school. For this objective to be reached, four specific objectives were established which discussed the identification of the conceptions of the teachers about infancy in school aspects; the identification of the social and educational relationships of children in the school through play; analysis of the academic works on infancy in contemporary society; as well as the identification of the games most used in schools. The survey was carried out at the Vila da Felicidade Municipal School, whose unusual location on the west side of Manaus in the Mauzinho district close to the CEASA port, made it possible to analyse different infantile manifestations because of the geographic location of the community where the school is located which permits an intimate relationship with the Solimões river and the communities on the other side of the river. This relationship is also present in the fabric of the classroom because there are students that live in the Catalão community which cross the river every day to study and share their experiences, stories and infancy with the children from this side of the river. The subjects of the survey were 147 students of the school and their respective teachers. The teachers and the students were considered collective subjects. The method consisted of participant observation of the leisure times and spaces with an ethnographic register in the field notebook. Training sessions and debates were carried out with the teachers so that they could discuss themes such as how the school figures as a play space; play as an educational strategy and the experiences of play between teacher and student. The observations of the leisure space at Vila da Felicidade, the patio, doesn’t provide the desirable material conditions necessary for the development of play activities, leisure or games and only five types of games were recorded: policeman and thief; soccer; hide and seek; dodge ball; and play house which are developed from the child’s imagination. Through the arguments presented, it is possible to deduce ways to comprehend the capacity for play that are natural, unmentioned by the teachers, in which roles should be assumed in relation to their constitution and development. It was observed that all of the empirical elements available led us to believe that the sessions have little or no impact on the ways that the teacher analyses the inclusion of play activities in daily school life. It was possible to comprehend that despite the scientific and academic comprehension of the teachers about play and its representations in the pedagogical work classically linked to prioritizing reading, writing, math activities, systematic investments in school notebooks, regular homework, report cards, which make up the obligatory part of the educational system for the parents has made teaching practice difficult to change in regard to play and infant culture. Emphasize the inter-relations between culture and cognition, the interlinking of socio-cultural processes put into action while playing and those demanded in the practices of the production of narratives, in the process of elaborating scientific concepts, can be configured as a promising strategy in order to bring the parents closer to a more conscious position about the importance of innovations in school culture. Certainly, it’s not just up to the teacher to create these arguments working alone. It must be understood that everyone, committed to the construction of a school and infancy of high quality, must be involved in this process, above all in what we refer to as the proposition of the theme in the areas of teaching training.
Keywords: Crianças - Recreação; Sociologia da infância; Ressignificação cultural; Children - recreation; Sociology of childhood; Cultural reframing; OUTROS